O VERDE ABALOU O MURO - Cassol, Paulo Barrozo (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704211 It is a reflective and theoretical study based on the literature on the movement in defense of theenvironment that began in the twentieth century, changed systems, build national andinternational laws. Shaking the walls of capitalism, in pursuit of changes in environmentalprotection and quality of life. In this process, environmental education has been and remains thefundamental element in the search for a sustainable economy, inserted perfectly in this globalizedera.